Humanist foundations for the transformations of higher education under supercomplexity - Юрій Мєлков; Євген Пінчук (Філософія освіти)
The article is dedicated to the philosophical analysis of today’s higher education and the grounds and trends of its transformations, both on-going and desirable for the near future. The authors review the current social situation of supercomplexity and argue that under a perspective of unpredictable and changeable world the aim of higher education can no longer be seen in providing certain sets of skills and knowledge – instead, in the scope of the dialectics of traditions and innovations, such a situation implies “reinventing” the classical European idea of university that presupposes the all-round development of human personality and education of a cultural person as opposed to the approach based on professional skills only. Following the declarations of UNESCO, World Economic Forum and other international organizations on the transformations of higher education, it could be concluded that the foundations of such transformations are that of the classical ideas of humanism. The authors turn to the historical analysis of the humanist ideal in education (as well as of its criticism) since the Renaissance to the present day, especially noting Kant’s ideas as the grounds for understanding humanism as the concept that affirms the universal equality of all human beings, as the idea of the autonomy of a human and his or her rights and responsibility for one’s life and for the objective world, as well as the idea of the priority of universal identity. It is argued that based on such premises the trends for the transformation of higher education could be outlined as institutional transformations of universities towards deformalization, decentralization and humanization, as well as the necessity to develop an open education system based on anticipatory education that has its goal in shaping universal human qualities.